The Fate of the Roman Law in the Eastern Europe since the Death of Justinian the Great until the Fall of the Byzantine Empire - Karol Ryszkowski (Societas et Iurisprudentia, 2020)
To maintain the unity of the state and the legal order, Justinian banned the writing of abstracts, excerpts and interpretations of his codification. Justinian’s bans were subject to high penalties; however, they were already violated during his lifetime, which contributed to the development of legal thought. The durability of Justinian’s codification, as evidenced by long period of validity, was only apparent, because the Justinian law was only in force in later periods theoretically and in the form of extracts from extracts, including the Eclogue, Basilika, Novels of Leo VI, Procheiron and Epanagoge. The Eastern Church had far-reaching privileges under the imperial law, so it made sure that it was not lost by the desuetude. To this end, separate sets of provisions were created, whether included only in the imperial constitutions or provisions contained in all Justinian legislation. In the 7th Century, these collections combined collections of the Byzantine emperors – translated into the Old Russian by the state law for the Church with the provisions of the church legislation – canons (nomocanons). The apparatus of power in Byzantium deviated from its Roman standards. An important thread in the development of the Roman law in the Eastern Europe was its didactics. In the beginning, the problem was to eliminate scientific centres in Athens and Alexandria, which were opposing the Justinian codification. The consequence of the collapse of schools in Byzantium was the collapse of scientific development of the Roman-Byzantine law in the Eastern Europe. The lack of schools that could deal with the development of the Roman law also hindered its reception in Russia and the Balkan Peninsula, but in Greece Hexabiblos lasted until year 1946.